IMPLEMENTATION OF PLAY-BASED TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS AT DARUL AULAAD NURSERY - NIK AULIA INSYIRAH ISMAIL; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study examines the teaching and learning approach (PdP) for infants and toddlers at TASKA and its relationship with the aspirations of today's parents. This qualitative study uses semi-structured interviews with TASKA teachers and is supported by highlights from early childhood education literature. The results of the study show that the main approach used is learning through play and child-centered activities, which are proven to help children's language, physical, social, emotional and self-confidence development. Parents' aspirations are now not only focused on safety aspects, but also emphasize the development of communication, socialization and readiness for preschool. However, some challenges were identified such as high teacher-child ratios, differences in individual developmental levels and time constraints that affect the effectiveness of PdP. Overall, the existing approach is seen to be successful in meeting the majority of parents' expectations, but still requires improvement in terms of communication, teacher training and parent cooperation to support the holistic development of children.